Conflitos conjugais e seus efeitos sobre o comportamento de crianças: Uma revisão teórica - Villas Boas, Ana Carolina Villares Barral; Dessen, Maria Auxiliadora; Melchiori, Lígia Ebner [UNESP] (My University, 2010)
Marital conflicts have been largely investigated in research, especially because of its impact on child development. Based on a literature review, this article aims to present some reflections about marital conflicts and its possible associations with children's behavior, particularly through parental practices. Emphasis is made on a systemic view of causality between marital conflict and child behavior, which offers a better comprehension of the family functioning. This perspective also allows us to enlarge the analysis scope beyond linear correlations between both variables.
Marital conflict and its effects on children's behavior: A theoretical review
Keywords: Child development; Family; Marital conflict